Pengelolaan Kegugupan Berbicara Di Depan Umum Bagi Anak-Anak Sekolah Di Panti Asuhan Holy Angel, Bekasi - Christanti, Maria Febiana; Mardani, Puri Bestari; MBP, Ratu Laura (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
This manuscript presents the outcome of community service activities for children at Holy Angel orphanage who experiences nervousness when public speaking. The team focuses on middle and high school participants who often make presentations in front of the class. In the previous community service, we discussed training regarding increasing students' self-confidence. The team complemented the idea of public communication on intrapersonal strength, namely managing nervousness with an emphasis on practice, preparation, and the ability to overcome nervousness constructively. The team believes that knowledge of managing nervousness from an early age can help children in orphanages get used to facing various kinds of audiences in the future. This service method is tests, lectures and practice which include assignments and simulations. The result of this activity is that children can overcome nervousness by means of positive self-motivation, regular breathing, good script preparation and analyzing the audience. Keywords: public communication, public speaking, nervous management, communication anxiety